EKSTRAK DAUN KALIANDRA SEBAGAI INHIBITOR ALAMI LAJU KOROSI ST-37 - Moh. Jufri; Indra Surya; Ali Saifullah; Suwarsono Suwarsono; Rr. Heni Hendaryati; Sudarman Sudarman (ROTOR, 2022)
The utilization of natural resources as a metal inhibitor is widely researched. The extract of Calliandra leaves is one of the natural resources utilized to prevent the corrosion rate. It contains high tannins, which is a natural compound that can be utilized as an inhibitor of the corrosion rate. The research is aimed to find out the efficiency of Calliandra leaves extract as the natural inhibitor for steel ST-37. The experiment method is applied to vary the extract of Calliandra leaves in the corrosive medium. Meanwhile, the extraction of Calliandra leaves uses the maceration method. The extraction of Calliandra leaves with the solvent uses an evaporation process using a rotary vacuum evaporator. The extract used as the inhibitor is determined in 5%, 10%, and 20% of concentrations. The sample test of corrosion used is steel ST-37 with 4 × 4 cm of dimension and 0.2 cm of thickness. The best inhibition efficiency is 99.73% with an inhibition concentration of 20% in HCl. It shows that the extract of Calliandra leaves works well as an inhibitor, and it is efficient to inhibit the corrosion rate.